Konsep Ummatan Wasathan dalam Perspektif Tafsir Nusantara (Tafsir An-Nur, Tafsir Al-Azhar, dan Tafsir Al-Misbah) - Nuryansah, Mohamad; Haq, Muhammad Izzul (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
AbstractThis study aims to explain the notion of ummatan wasathan from an Indonesian perspective. This principle is critical to comprehend and apply in the face of the ongoing challenge of radicalism and liberalism. Individuals and groups are at odds as a result of radicalism and liberalism. There must be a resolution so that the disagreement does not last for a long time; one option is to adopt the concept of ummatan wasathan, or people in the middle. This study is a library research article using a descriptive analysis approach. The essential data is in the form of wasthan terms in interpreting An-Nur, al-Azhar, and Al-Misbah. The following are the study's findings: According to An-Nur's interpretation, ummatan wasathan are the best-chosen people because they are fair, balanced, not overly religious, and do not lack in worship. Then, according to Al-Azhar's interpretation, ummatan wasathan are those who are in the middle, who do not lean towards the world or the hereafter, who always take the straight path, and who are not mainly concerned with the spiritual and forget the physical. Furthermore, Al-Misbah's interpretation explains that ummatan wasathan (middle) is just, chosen, moderate, and excellent people. They pursue the middle path and are constantly thankful for life.Keywords: Concept; Indonesian Interpretation; Ummatan Wasathan. AbstrakTulisan ini bertujuan untuk mengungkap konsep ummatan wasathan dalam perspektif tafsir Indonesia. Konsep tersebut penting untuk dipahami dan diimplementasikan di tengah gempuran radikalisme dan liberalisme yang terus mengancam. Radikalisme dan liberalisme menyebabkan munculnya konflik antar individu maupun kelompok. Perlu adanya penyelesaian agar konflik tidak berlangsung secara berkepanjangan, salah satu caranya dengan mengimplementasikan konsep ummatan wasathan yaitu umat yang berada di tengah-tengah. Tulisan ini merupakan penelitian kepustakaan (library research) dengan pendekatan diskriptif analisis. Data utamanya berupa term ummatan wasthan dalam tafsir An-Nur, tafsir al-Azhar dan tafsir Al-Misbah. Temuan dalam tulisan ini yaitu: Pada Tafsir An-Nur dijelaskan bahwa ummatan wasathan merupakan kaum pilihan yang paling baik, bersikap adil, seimbang, tidak berlebihan dalam beragama dan juga tidak kurang dalam beribadah. Kemudian dalam Tafsir Al-Azhar disebutkan, ummatan wasathan adalah umat yang berada ditengah-tengah, tidak condong ke dunia maupun akhirat, selalu menempuh jalan yang lurus, serta bukan semata-mata mementingkan rohani sehingga melupakan jasmani. Sedangkan Tafsir Al-Misbah menjelaskan bahwa ummatan wasathan (pertengahan) merupakan umat yang adil dan pilihan, umat yang moderat dan teladan. Mereka menempuh jalan tengah dan selalu bersyukur menerima hidup. Kata Kunci: Konsep; Tafsir Indonesia; Ummatan Wasathan.